A clustering-based multi-setting overcurrent protection approach with optimisation and experimental validation for distribution networks - Feras Alasali; Mohamed Salem; Haytham Y. Mustafa; Hassen Loukil; Naser El-Naily; Abdelaziz Salah Saidi; William Holderbaum (International Journal of Electrical Power & Energy Systems, 2025)
This study presents an advanced multi-setting adaptive Overcurrent Relays (OCRs) protection scheme for distribution networks experiencing frequent topological changes and high penetration of distributed generation. Conventional relays, constrained by their limited setting group, are unable to respond effectively to such dynamic conditions. To overcome this, the network is first classified into four representative operating states using clustering algorithms, including K-Means, Hierarchical, and Fuzzy C-Means, based on fault current behaviour and the general tripping time of OCRs. This work involves integrating clustering-based topology grouping with bio-inspired optimisation techniques, specifically the Water Cycle Algorithm (WCA) and the Transit Search Algorithm (TSA), to assign optimised Time Multiply Settings (TMS) values for each relay group, ensuring fast and coordinated protection without reliance on continuous communication or centralised control. Simulation results demonstrate that TSA outperforms WCA in both tripping time reduction and computational efficiency, with notable improvements observed in complex relay coordination across various 12-power network topologies with Distributed Energy Resources (DERs). The proposed strategy is validated through simulation and experimental validation, utilising testing setups that employ the OMICRON CMC-156 and SIPROTEC 7SJ62 relay. The observed trip time for OCR 12 was 0.7 s, confirming the accuracy of the real equipment’s response. Overall, the method enhances protection flexibility, reduces response time, and supports reliable operation under varying grid conditions.